2016
DOI: 10.4244/eij-d-15-00192
|View full text |Cite
|
Sign up to set email alerts
|

Emergency percutaneous implantation of veno-arterial extracorporeal membrane oxygenation in the catheterisation laboratory

Abstract: Fluoroscopy-guided emergency implantation of femoral VA ECMO by an interventional cardiologist in the catheterisation laboratory is effective and safe for both patients in cardiogenic shock and those in refractory cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In more recent times, the circuits have become smaller, and there has been a shift to percutaneous access as opposed to open access. In some hospitals, the cardiac catheterization lab is the preferred location given the ease of fluoroscopy and the availability of various wires and sheaths/dilators [ 45 ]. In other hospitals, the operating room is the preferred location, potentially with portable fluoroscopy or the use of trans-esophageal echocardiography for the placement of the long venous cannula.…”
Section: Where Is Ecmo Performedmentioning
confidence: 99%
“…In more recent times, the circuits have become smaller, and there has been a shift to percutaneous access as opposed to open access. In some hospitals, the cardiac catheterization lab is the preferred location given the ease of fluoroscopy and the availability of various wires and sheaths/dilators [ 45 ]. In other hospitals, the operating room is the preferred location, potentially with portable fluoroscopy or the use of trans-esophageal echocardiography for the placement of the long venous cannula.…”
Section: Where Is Ecmo Performedmentioning
confidence: 99%
“…Our results were similar for the aforementioned complications. Interestingly, installation by experienced operators in the CCL does not seem to produce a higher rate of vascular complications as compared to surgical implantation in the OR 11 .…”
Section: Discussionmentioning
confidence: 87%
“…Prior studies in patients undergoing interventional cardiology procedures have described lower in-hospital survival rates despite implementation of VA-ECMO programs in the CCL. In patients with acute myocardial infarction experiencing refractory CS, several cases series reported survival rates of 22%-65% after peripheral VA-ECMO [11][12][13][14][15][16][17] . In patients suffering hemodynamic complications during TAVR, rescue VA-ECMO support produced in-hospital survival rates of 44%-75% [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clear benefit of mechanical support, there is a paucity of data regarding emergency use of VA-ECMO in the catheterization laboratory. Few case reports showed that ECMO is becoming increasing available also in this setting and may represent an effective temporizing measure/bridge to the final therapeutic intervention, such as PCI or surgery, that could solve the reversible cause of cardiac arrest (1) [13][14][15]. In 14 cases of refractory cardiac arrest during PCI or TAVI (Transcatheter Aortic Valve Implantation), ECPR using percutaneous VA-ECMO allowed to restore circulation in all patients, with 50% of survival at hospital discharge [11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surgical ECMO implantation by vessel exposure has been gradually replaced by percutaneous techniques. Indeed, it has been demonstrated that fluoroscopy-guided emergency percutaneous implantation of femoral VA-ECMO can be effectively and safely done by an interventional cardiologist in the catheterization laboratory [14]. Unfortunately, ECMO is still associated with a broad [11,12].…”
Section: Discussionmentioning
confidence: 99%